Differential modulation of cognitive control networks by monetary reward and punishment. Issue 3 (28th January 2019) - Cubillo, Ana; Makwana, Aidan B; Hare, Todd A
Abstract: Incentives are primary determinants of if and how well an organism will perform a given behavior. Here, we examined how incentive valence and magnitude influence task switching, a critical cognitive control process, and test the predictions that the anterior cingulate cortex (ACC) and the ventral striatum (vStr) function as key nodes linking motivation and control systems in the brain. Our results indicate that reward and punishment incentives have both common and distinct effects on cognitive control at the behavioral and neurobiological levels. For example, reward incentives led to greater activity in the ACC during the engagement of control relative to punishments. Furthermore, the neural responses to reward and punishment differed as a function of individual sensitivity to each incentive valence. Functional connectivity analyses suggest a role for vStr in signaling motivational value during cognitive control and as a potential link between motivation and control networks. Overall, our findings suggest that similar changes in observed behavior (e.g. response accuracy) under reward and punishment incentives are mediated by, at least partially, distinct neurobiological substrates.